PENGARUH PENDAMPINGAN KADER TERHADAP PERILAKU GIZI IBU DAN STATUS GIZI BALITA - Mars Khendra Kusfriyadi; Sugiyanto Sugiyanto; Fretika Utami Dewi (Poltekkes Kemenkes Kalimantan Timur, 2019)
South Barito Regency with the problem of the prevalence of malnutrition reached 30.6%, the problem of short / very short and thin/very thin children was 33.6% and 18.3% respectively, far exceeding the provincial and national figures so it was necessary to get attention. Therefore, it is recommended that appropriate interventions in addressing these nutritional problems are by increasing the role of sensitive interventions and supplementary feeding. The research included quasi-experiments with designs before and after intervention with comparison groups. The study was carried out in two sub-districts. Data analysis used independent t-test and Chi-square. There were significant differences between maternal behavior after cadre mentoring in the intervention group and maternal behavior in the comparison group (p-value=0,000). There was a significant difference in behavior improvement between the intervention groups and the comparison group with (p-value=0,000). There are significant differences in the increase in underweight children after mentoring cadres with supplementary feeding. There is an influence of cadre assistance on maternal behavior in South Barito District. There is an influence of cadre assistance on the nutritional status of children in South Barito District.